Mathematical modeling of a clinical waste incineration process - Arshad, Khairil Anuar; Ahmad, Tahir; Baharun, Sabariah (Faculty of Science, 2006)
At present, there is no fundamentally based mathematical model of the incineration process of clinical waste. The development of an accurate mathematical model of the process is being hampered by the lack of measured data for validation due to its complexity feature. Due to the wide applications of the graph theory, a study was carried out to model a clinical waste incineration process using graph theory. Initially, a graphical model was constructed to explain the connections of the variables in the incinerator, which serves as a basis for a more dynamic graphical representation of the system. This model was found to be an Autocatalytic Set (ACS), conforming to the key feature of the model proposed by Jain and Krishna. Their model was then adopted and modified to suit the incineration process, which has resulted in a model explaining the two dynamics of the incineration process, that is, the concentration dynamics and the graph dynamics of the system. The former described the rate of change of the variables or species and the latter represented the evolution of the species in the incineration process.